Species Richness and Habitat Suitability of Myrmecophytes in Bengkulu : Host Tree, Coexist Epiphytes and Animals - Safniyeti Safniyeti; Sulistijorini Sulistijorini; Tatik Chikmawati (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Myrmecophytes or locally known as simbagh utak are common medicinal plants used by locals in Bengkulu, especially in South Bengkulu, for treating various diseases. Despite their potential as medicines, there is no report on biotic factors can be used to indicate of Myrmecophytes species’ richness and habitat suitability. The objectives of this research were to analyze the Myrmecophytes’ species richness and habitat suitability. This study used the purposive sampling method by exploring the area where Myrmecophytes were commonly found. The biotic factors of Myrmecophytes were analyzed by identifying the tree host, the other epiphyte plant grew around them, and animal occupants on the tuber of the Myrmecophytes. The Myrmecophytes distribution was analyzed by using ArcGIS10.1. The results showed that there were two species of Myrmecophytes, namely Hydnophytum formicarum and Myrmecodia tuberosa in the study area. The Myrmecophytes attached and hung in 9 species of host trees. The characteristics of host trees are high trees with large diameter, mostly rough-barked; some were cracked and mossy. The highest frequency of host trees included Hevea brasiliensis and Durio zibethinus. Myrmecophytes coexisted with 12 species of epiphytes. Epiphyte plants like Dendrobium sp. and Drymoglossum piloselloides can be used to indicate the presence of Myrmecophytes. Ants made up the most predominantly animal found living inside the tubers of Myrmecophytes, with some cockroaches and termites found at the tuber of Hydnophytum. Information on species' richness and habitat suitability of Myrmecophytes can serve as supporting data for conservation efforts in Bengkulu to prevent the extinction of this species.